(untitled) (Faridpur Medical College Journal, 2014)
Ectopic pregnancy is a condition where gestation sac is located outside the uterine cavity; it is a major life threatening situation in early pregnancy. A cornual pregnancy is an ectopic pregnancy that develops in the interstitial portion of the fallopian tube invading through the uterine wall. As myometrium is more distensible fallopian tube cornual pregnancies often rupture later than other tubal pregnancies. Cornual pregnancy is rare and carries grave consequences to both mother and fetus. Here a case report has been presented where the patient was admitted in Faridpur Medical College Hospital. The case was presented with intra-abdominal haemorrhage at second trimester. In this cases investigation missed the diagnosis, final diagnosis was only made after laparotomy. The need for clinical suspicion and role of ultrasonography, resuscitation and laparotomy is necessary to prevent catastrophe. DOI: http://dx.doi.org/10.3329/fmcj.v8i2.20397 Faridpur Med. Coll. J. 2013;8(2): 102-104